ANALISIS EFEKTIVITAS PENGENDALIAN INTERNAL TERHADAP PENERIMAAN DAN PENGELUARAN KAS PADA PT XYZ - Shafira Salwa Zahrani; Indrawati Yuhertiana (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to evaluate the effectiveness of the internal control system on the cash receipt and disbursement process at PT XYZ. The approach used in this study is a qualitative descriptive method with a case study technique, which allows researchers to dig up in-depth information through direct interviews with related parties, observation of operational activities, and review of supporting documents. From the results of the analysis carried out, it is known that the cash control system implemented by the company has included the main elements of internal control, such as the separation of responsibilities between parties who authorize, record, and store cash; clear transaction authorization procedures; orderly and timely transaction recording; and routine supervision by management. This shows that in general, the company has implemented good internal control principles. However, this study also found several weaknesses in certain aspects, such as less than optimal documentation of certain transactions and the absence of periodic job rotation that can prevent potential abuse of authority. Therefore, it is recommended that the company conduct periodic evaluations and improvements to improve the effectiveness of the existing cash control system, so as to minimize risks and maintain the integrity of the company's financial information.